A Critical Review on Thermo-Sensitive Vaginal Gel for the Foundation of Preparing Thermo-Sensitive Vaginal Gel of PVK (Panchvalkal Kashaya) Extract (International Journal of Ayurveda and Pharma Research, 2022)
RTI (Reproductive Tract Infection) is the vital cause of suffering in women and neonates. According to WHO estimation 340 million new cases of curable STI (Sexually Transmitted Disease) other than HIV/AIDS occurs every year, most of which are occurring in developing countries. Genital tract infection is the prime cause of most gynaecological disease. Vaginal candidiasis is the most common cause of Genital tract infection. It (Vaginal candidiasis) is a common condition and up to 75% of all women suffer at least one episode of this infection during their life time. For treating the pathological condition of genital tract, direct application or self application of medicine is very difficult and the residence time of the medicine is less due to self cleansing properties of vaginal canal. Application of the drug in other route may cause systemic adverse reaction. To overcome this arduous situation, in situ thermo-sensitive gel form has great importance. In this article an attempt have been made for the review of the thermo-sensitive vaginal gel and the scholar has gathered the basic knowledge to develop an Ayurvedic formulation Panchavalkal kashaya thermo-sensitive vaginal gel by this review. This work will be done in School of Pharmaceutical Science, Shoolini University, Solan, HP.